Effect of temperature on salt-salt aqueous biphasic systems: manifestations of upper critical solution temperature - Dilip, Meghna; Bridges, Nicholas J.; Rodriguez, Hector; Pereira, Jorge Fernando Brandão [UNESP]; Rogers, Robin D. (Springer, 2015)
Water-miscible ionic liquids (ILs) may be salted out using kosmotropic salts such as potassium phosphate (K3PO4) to form salt-salt aqueous biphasic systems (ABS). The effect of temperature on these systems has been studied using phase diagrams and it is observed that the degree of binodal shift decreases (requiring lower IL and kosmotropic salt concentrations) with the increase of temperature following the trend [C(4)mim]Cl > [C(4)py]Cl > [C(4)mmim] Cl > [N-4444]Cl. This trend can be correlated with the decreasing hydrogen bonding abilities of each salt. The phase behavior was also interpreted on the basis of critical solution temperature behavior of pure aqueous ionic liquid solutions. Additionally, the distribution of alcohols in these systems was studied as a function of temperature and it was found that the distribution ratios did not change with changes in temperature. The Gibbs energy of transfer of a methylene group in these systems and correlation to tie-line length was also determined. It was concluded that while the miscibility of alcohols increases in the ILs with increasing temperature, phase divergence in the aqueous biphasic system decreases, and thus these competing forces tend to cancel each other out for small polar molecules. A comparison is provided for the response to temperature in the currently studied salt-salt systems and analogous ABS formed by the addition of hydrophilic polymers to kosmotropic salts (polymer-salt) or other polymers (polymer-polymer).
Keywords: Aqueous biphasic systems; Ionic liquids; Upper critical solution temperature; Separation